The elderly and the right to an active aging: the strategy of social cohousing to counteract relational poverty - Carrera, Letizia (Frontiers in Sociology, 2024)
The older citizens represent a portion of the population that is not only already high but is also expected to increase according to trend analyses from major national and international research reports. The pandemic experience has shown how they feel the scarcity of relationships and the loneliness of their homes as factors that significantly impact the quality of their daily lives. This challenging historical moment has provided an opportunity to implement a series of projects specifically dedicated to those over 65, aiming to ensure a full range of possibilities for them, starting from highly “enabling” processes. In this perspective, the theme of social senior housing and its various manifestations represents a key strategy to counteract relational poverty, toward intervening in the level of social sustainability through multi-actor network pathways that bring together institutions, private entities, third sector, and research centers. The article aims to analyze the potential that the senior cohousing model can offer, as well as the difficulties this type of shared living arrangement faces—moreover when designed specifically for older individuals and supported by public administrations—, and which still makes it an almost experimental experience in Italy.